Improving the micronuclei test in cultured lymphocytes by gradient and cell spreading methodology - Castillo, Erika (2011)
The micronuclei test in lymphocyte culture is a validated procedure to study mutagenicity. It consists in detecting damaged interphasic nuclear material produced by chromosome fragmentation or nuclear division errors in 2000 binucleated cells with well defined cytoplasm. Standard protocol derives from blood chromosome preparation with hypotonic and fixing solutions as well as preparing slides by dropping fixed cells. We modified the protocol to improve the number and quality of micronuclei. First, lymphocytes are separated from red cells before culture. After 72 hours, hypotonic and repeated fixer washing steps are eliminated. Cells are put onto slides by spreading instead of dropping. With these modifications we obtained more (about 8 times per slide) and better defined binucleated cells to help micronuclei detection.